TEKTONO-STRATIGRAFI BAGIAN TIMUR SULAWESI - Hermes Panggabean; Surono Surono (Pusat Survei Geologi, 2011)
Basement rocks of eastern part of Sulawesi, from the East Arm to Southeast Arm, are composed of continental and ophiolite origins, which were collided in latest Oligocene – Middle Miocene. After collision, extention occurred in the area that formed a deepening basin in where Sulawesi Molasse was deposited. Some continental terranes distributed in the eastern Sulawesi, could be derived from northern magin of Australia, and the ophiolite was a part of the Pacific Ocean.Key words: ofiolite, continental terrane, collision and basin